Feasibility study of a quick cure process using a conventional belt furnace - Kwan, Yew Kee. (2009)
Over the years, die attach of cerdip packages had transformed from eutectic die bonding to silver glass die attach. But this material had a drawback. It had to be cured in a furnace at a temperature >400°C and its cycle time was generally about an hour. For optimal cure, the furnace profile was critical. In a typical cerdip assembly process, cure and sealwere 2 processes that attributed the longest cycle time. Rapid cure was a possible solution to cycle time reduction. Presently, technology was available for plastic packages but not for cerdip. The author visualised that rapid cure would revolutionarise die attach curing process for ceramic packages once a production model was available. The criterion for rapid cure was short cure time.